2024
DOI: 10.1039/d3sc04411d
|View full text |Cite
|
Sign up to set email alerts
|

CoeffNet: predicting activation barriers through a chemically-interpretable, equivariant and physically constrained graph neural network

Sudarshan Vijay,
Maxwell C. Venetos,
Evan Walter Clark Spotte-Smith
et al.

Abstract: CoeffNet uses coefficients of molecular orbitals of reactants and products to predict activation barriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Despite these advances for molecular property prediction, the prediction of computed reaction properties (principally, reaction barriers ,, ) is still in its infancy . Machine learning approaches span from utilizing simple two-dimensional fingerprints of reaction components , (reactants and products) to physical-organic descriptors, ,,,, or electronic structure-inspired features, to transformer models , adapted for regression, and 2D graph-based approaches. ,,, The latter, particularly the ChemProp model, , are often best-in-class in predicting reaction properties . It has been shown that these models achieve their impressive performance by exploiting atom-mapping information, which provide information analogous to the reaction mechanism.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite these advances for molecular property prediction, the prediction of computed reaction properties (principally, reaction barriers ,, ) is still in its infancy . Machine learning approaches span from utilizing simple two-dimensional fingerprints of reaction components , (reactants and products) to physical-organic descriptors, ,,,, or electronic structure-inspired features, to transformer models , adapted for regression, and 2D graph-based approaches. ,,, The latter, particularly the ChemProp model, , are often best-in-class in predicting reaction properties . It has been shown that these models achieve their impressive performance by exploiting atom-mapping information, which provide information analogous to the reaction mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Another category of reaction fingerprints arises from discretization of physically inspired functions ,, constructed using a cheap estimate of the transition state (TS) structure or rather the structures of the reaction components ,, The SLATM d representation , in particular has been shown to yield accurate predictions of reaction barriers, particularly for data sets , relying on subtle changes in the geometry of reactants and/or products. End-to-end models based on three-dimensional structures of reactants and products have also recently emerged. ,, In a different vein, several works aim to directly predict the TS structure, which together with the reactant structure gives the reaction barrier. These approaches lie outside the scope of the property prediction focus here.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation